Complete chloroplast genome of Saprosma merrillii Lo. (Rubiaceae): A Near Threaten (NT) shrub species endemic to Hainan province, China. Issue 1 (2nd January 2019) - Zhu, Zhi-Xin; Wang, Jian-Hua; Zhao, Kun-Kun; Fan, Wei-Wei; Wang, Hong-Xin; Wang, Hua-Feng
Abstract: Saprosma merrillii is a plant of the family Rubiaceae. So far, there is no study on the genome of S. merrillii. Here, we report and characterize the complete plastid genome sequence of S. merrillii in an effort to provide genomic resources useful for promoting its conservation. The complete plastome is 155, 820 bp in length and contains the typical structure and gene content of angiosperm plastome, including two Inverted Repeat (IR) regions of 26, 228 bp, a Large Single-Copy (LSC) region of 85, 625 bp and a Small Single-Copy (SSC) region of 17, 739 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA genes, and 4 unique rRNA genes. The overall A/T content in the plastome of S. merrillii is 62.50%. The complete plastome sequence of S. merrillii will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies for Rubiaceae.